2019
DOI: 10.1002/jcp.28446
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin exerts protective effects against atherosclerosis in rats by regulating the Hippo–FOXO3A and PI3K/AKT signaling pathways

Abstract: Atherosclerosis (AS), a progressive disorder, is one of the tough challenges in the clinic. Scutellarin, an extract from Herba Erigerontis, is found to have oxygen‐free radicals scavenging effects and antioxidant effects. In this study, we aimed to investigate the anti‐AS effects of scutellarin is related to controlling the Hippo–FOXO3A and PI3K/AKT signal pathway. To establish an AS model, the rats in the scutellarin and model groups were intraperitoneally injected with vitamin D 3 and then fed a high‐fat die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…VECs. Recent studies have revealed that Ang II increases EC YAP phosphorylation (23), and that angiotensin-converting enzyme 2 activation attenuates pulmonary vascular remodeling via the induction of pulmonary arterial cell apoptosis by upregulating YAP phosphorylation (24). The present results were consistent with these recent studies because they indicated that Ang II increased YAP phosphorylation and regulated VEC activity.…”
Section: Discussionsupporting
confidence: 92%
“…VECs. Recent studies have revealed that Ang II increases EC YAP phosphorylation (23), and that angiotensin-converting enzyme 2 activation attenuates pulmonary vascular remodeling via the induction of pulmonary arterial cell apoptosis by upregulating YAP phosphorylation (24). The present results were consistent with these recent studies because they indicated that Ang II increased YAP phosphorylation and regulated VEC activity.…”
Section: Discussionsupporting
confidence: 92%
“…Rats in the control group were fed a normal diet, whereas all other rats were fed a high-fat diet and vitamin D 3 to induce AS (the composition of the rat diet is listed in Table S1) and was in accordance with the literature. 23,24,25 Food was provided adlibitum. After allowing the rats to acclimatize for in the corresponding group.…”
Section: Laboratory Animals and Groupingmentioning
confidence: 99%
“…Notably, the atheroprotective effect of steady laminar flow in major arteries is linked with inhibition of Hippo/YAP effector function[ 228 ] while activation of this pathway is linked with vascular remodelling, and switching of arterial smooth muscle cells to the “synthetic” proliferative phenotype in response to biochemical stretch[ 229 ]. The effector function of YAP is linked with accelerated atherosclerosis in apoE -/- mice[ 230 ], while the herbal extract Scutellarin can protect against atherosclerosis in rats by modulating the Hippo-YAP-Forkhead box (FOXO)3A transduction pathway[ 231 ].…”
Section: Epigenetic Mechanisms Contributing To “Foam Cell” Formation:mentioning
confidence: 99%